Inverted Supinator Reflex - Kazuhiro Kamata; Katsuo Yamanaka (Annals of Internal Medicine: Clinical Cases)
A 77-year-old woman developed progressive numbness in her arms that extended bilaterally from the hands to the forearms. She had a positive inverted supinator sign, indicating inverted supinator reflex, which led to a diagnosis of cervical spondylosis myelopathy.